PENGARUH KOMUNIKASI PERSUASIF, ON JOB TRAINING DAN PERAN PEMIMPIN INFORMASIONAL DALAM MENINGKATKAN KUALITAS KERJA KARYAWAN - Ramadhan, Muhamad Yudha; Subiyanto, Didik; Septyarini, Epsilandri (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
Human resources are an asset for an organization's success and efficiency in attaining its vision and goals. Work quality will be a critical organizational factor. The purpose of this study was to discover the impact of persuasive communication, on-the-job training, and the function of informative leaders in increasing employee work quality. The research strategy employs quantitative survey methods. The study was conducted at the Dompu Regency Road Traffic and Transportation Service with a population of 200 people and a sample size of 134. The accidental sampling approach was used, along with a questionnaire study instrument. Instrument testing, including validity and reliability tests. Normality, multicollinearity, and heteroscedasticity tests are used to evaluate data requirements. Data analysis with multiple linear regression, statistical testing using partial tests, simultaneous tests and determination coefficient tests. According to the study's findings, leadership information and on-the-job training have considerable beneficial effects on employee work quality while persuasive communication has a marginally good effect. The findings of simultaneous tests reveal that they collectively have a considerable impact on the productivity of personnel at the Dompu Regency Road Traffic and Transportation Service.